Radiographic image interpretation by Australian radiographers: a systematic review - Andrew Murphy; Ernest Ekpo; Thomas Steffens; Michael J. Neep (Journal of Medical Radiation Sciences, 2019)
Abstract Introduction Radiographer image evaluation methods such as the preliminary image evaluation (PIE), a formal comment describing radiographers’ findings in radiological images, are embedded in the contemporary radiographer role within Australia. However, perceptions surrounding both the capacity for Australian radiographers to adopt PIE and the barriers to its implementation are highly variable and seldom evidence‐based. This paper systematically reviews the literature to examine radiographic image interpretation by Australian radiographers and the barriers to implementation. Methods The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses were used to systematically review articles via Scopus, Ovid MEDLINE, PubMed, ScienceDirect and Informit. Articles were deemed eligible for inclusion if they were English language, peer‐reviewed and explored radiographic image interpretation by radiographers in the context of the Australian healthcare system. Letters to the editor, opinion pieces, reviews and reports were excluded. Results A total of 926 studies were screened for relevance, 19 articles met the inclusion criteria. The 19 articles consisted of 11 cohort studies, seven cross‐sectional surveys and one randomised control trial. Studies exploring radiographers’ image interpretation performance utilised a variety of methodological designs with accuracy, sensitivity and specificity values ranging from 57 to 98%, 45 to 98% and 68 to 98%, respectively. Primary barriers to radiographic image evaluation by radiographers included lack of accessible educational resources and support from both radiologists and radiographers. Conclusion Australian radiographers can undertake PIE; however, educational and clinical support barriers limit implementation. Access to targeted education and a clear definition of radiographers’ image evaluation role may drive a wider acceptance of radiographer image evaluation in Australia.